Kesejahteraan Psikologis Lansia Janda/Duda Ditinjau dari Persepsi Terhadap Dukungan Sosial dan Gender - Desiningrum, Dinie Ratri (Jurnal Psikologi, 2014)
AbstractThe death of spouse brings major changes in the life of the wife/husband that may affect their psychological well-being. To maintain their psychological well-being within an optimum level, elderly will seek sources of social support in their lives. This study aims to test the correlation between perceived social support and psychological well-being in elderly and to investigate gender differences in perceived social support and psychological well-being. This study comprised 112 elderly (78 widowers; 34 widows), members of the Healthy Elderly Community of the Indonesian Red Cross, Semarang City. Data were collected using the Perceived Social Support Scale (32 items; Î± = 0.97) and Psychological Well-being Scale (33 items; Î± = 0.92). Simple regression analysis was applied to test the correlation between two variables and student t-test was used to compare data from male and female groups. The results revealed a positive and significant correlation between perceived social support and psychological well-being in elderly (r = 0.739; p < 0.001). Perceived social support explained 54.6% of the psychological well-being. T-test revealed gender differences in perceived social support and psychological well-being in elderly. The widows perceived social support better than the widowers (t(35) = 3.594; p < 0.001), the widows also showed higher psychological well-being than the widowers (t(42) = 2.944; p= 0.004).